Floor and ceiling effects in the Oxford Shoulder Score: an analysis from the National Joint Registry. (1st November 2021) - Singh, Harvinder P.; Haque, Aziz; Taub, Nick; Modi, Amit; Armstrong, Alison; Rangan, Amar; Pandey, Radhakant
Abstract : Aims: The main objective of this study was to examine whether the Oxford Shoulder Score (OSS) demonstrated floor or ceiling effects when used to measure outcomes following shoulder arthroplasty in a large national cohort. Secondary objectives were to assess its pain and function subscales, and to identify independent predictors for patients achieving a postoperative ceiling score following shoulder arthroplasty. Methods: Secondary database analysis of the National Joint Registry (NJR), which included 48, 270 patients undergoing shoulder arthroplasty, was conducted. The primary outcome measure was the OSS. Secondary outcome measures were the OSS-Function Component Subscale and OSS-Pain Component Subscale. Floor and ceiling effects were considered to be present if > 15% of patients scored either the lowest or highest possible score. Logistic regression analysis was used to identify independent predictors for scoring the highest possible OSS score postoperatively. Results: Preoperatively, 1% of patients achieved the lowest possible OSS score (0) and 0.4% of patients achieved the highest possible score (48). Postoperatively, < 1% of patients achieved the lowest score at all timepoints, but the percentage achieving the highest score at six months was 8.3%, at three years 16.9%, and at five years 17%. Male patients, those aged between 60 and 89 years, and those undergoing an anatomical total shoulder arthroplasty (ATSA) were more likely to contribute to the ceiling effect seen in the OSS questionnaire. Pain and function subscales exhibited greater ceiling effects at three years and five years when compared with the overall OSS questionnaire. Logistic regression analysis showed that sex, procedure type, and preoperative OSS score were independent predictors for scoring the highest possible OSS at years. Conclusion: Based on NJR patient-reported outcome measures data, the OSS does not exhibit a ceiling effect at six months, but does at three years and five years, in part due to outcome scores of ATSA. Preoperative OSS, age, male sex, and ATSA are independent predictors of achieving a ceiling score. Cite this article: Bone Joint J  2021;103-B(11):1717–1724.